Emotions in Hellenistic Philosophy. - Knuuttila, Simo (New synthese historical library., 2010)
Discussions about the nature of the emotions in Hellenistic philosophy have aroused intense scholarly interest over the last few years. The topics covered by the essays in this volume range from the classical background of Hellenistic theories, through debates on emotion in the major Hellenistic schools, to discussions in later antiquity. Special emphasis is placed on the development of the Stoic views on the nature and value of the emotions. The essays are written with a high level of philosophical and classical scholarship, but contain no exclusive technicalities. Audience: This first comprehensive treatment of the emotions in Hellenistic philosophy can be read with pleasure and profit not only by professionals in ancient philosophy but also all those who are interested in the philosophy of mind and its history.